Termos Neológicos na obra de Brotero (1788) - Luana da Silva Borges (2024)
Félix Avellar Brotero’s “Compendium of Botany” (“Compêndio de Botânica”), published in Paris in 1788, had great importance at the time as a source of botanical knowledge in Portuguese. As the first book in Portuguese dedicated to botanical concepts and ideas, Brotero’s work was meant to translate definitions previously only available in Latin. Taking into account the Compendium’s importance for the history of the Portuguese language and the changes undergone by some lexical units over time, this study attempts to select from this relevant corpus lexical units lending themselves to more precise analyses – thus differing from the approach seen in the online version of the Houaiss dictionary (Houaiss, 2012). For these analyses, concepts from etymology (Viaro, 2011) were used to ground the criteria and steps used for the historical investigation of each lexical unit. Based on the principles of neology (Alves, 2011), properly characterized lexical units were then selected for further analysis of their word formation and meaning construction. With these analyses, this study aims to make a contribution to lexicographic studies by adding botanical entries extracted from Brotero’s work to the Portuguese-language “Historical Dictionary of Biology Terms” (“Dicionário Histórico de Termos da Biologia”) (Maroneze; Rio-Torto, 2023).